How to Reduce Mortality in crossbred calves - Upadhyay, Deepak; Gaur, G K; Mishra, Madhu; Singh, Mukesh; Bharti, P K (Indian Farming, 2017)
To reduce mortality in crossbred calves, adequate attention is required on nutrition, health care, housing, medication and inbreeding. Many diseases of newborn calves can be controlled by well-designed health management programs including the care and housing of dam during periparturient period, standard operating procedures for calving process and application of proper preventive measures (including sound nutritional programs). The five C’s (Colostrum, Cleanliness, Comfort, Calories and Consistency) provide an effective formula for managing the young dairy calf and to reduce the mortality within acceptable limit.